1998
DOI: 10.1046/j.1365-2842.1998.00333.x
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant mandibular and head‐neck movementsduring jaw opening–closing in man

Abstract: To test the hypothesis of a functional relationship between the human mandibular and cranio‐cervical motor systems, head‐neck movements during voluntary mandibular movements were studied in 10 healthy young adults, using a wireless optoelectronic system for three‐dimensional (3D) movement recording. The subjects, unaware of the underlying aim of the study, were instructed to perform maximal jaw opening–closing tasks at fast and slow speed. Movements were quantified as 3D movement amplitudes. A consistent findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
100
0
8

Year Published

2005
2005
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(117 citation statements)
references
References 44 publications
9
100
0
8
Order By: Relevance
“…In another study, the authors state that the bulk of the bolus and harder texture correlate with a greater head extension and greater amplitudes of mandible and head movement, during mastication (27) . Studies also show that extension, flexion and tipping movements of the head during chewing are expected (17,28,29) , reinforcing the existence of simultaneous and coordinated activity between the muscles of the neck and jaw (26) , although it is not clear how the regions affect one another (26) . In another study, the results showed exaggerated participation of perioral muscles and vertical jaw movements as movements associated with chewing, in institutionalized elderly (24) .…”
Section: Discussionmentioning
confidence: 99%
“…In another study, the authors state that the bulk of the bolus and harder texture correlate with a greater head extension and greater amplitudes of mandible and head movement, during mastication (27) . Studies also show that extension, flexion and tipping movements of the head during chewing are expected (17,28,29) , reinforcing the existence of simultaneous and coordinated activity between the muscles of the neck and jaw (26) , although it is not clear how the regions affect one another (26) . In another study, the results showed exaggerated participation of perioral muscles and vertical jaw movements as movements associated with chewing, in institutionalized elderly (24) .…”
Section: Discussionmentioning
confidence: 99%
“…Because there is a biomechanical relationship between the upper-cervical spine and the temporomandibular joint during active mouth opening, 7,51 it has been suggested that biomechanical adaptation of the jaw and the neck may be one possible reason why mouth opening increased after a cervical spine thrust manipulation. Nevertheless, the increase obtained in mouth opening following the atlanto-occipital manipulation cannot be considered as clinically relevant.…”
Section: Active Mouth Openingmentioning
confidence: 99%
“…The muscles of the jaw and the neck-shoulder complex have been observed to co-contract during mandibular movements and clenching (Davies, 1979;Clark et al, 1993;Widmalm et al, 1988). This integrated activation of jaw and neck muscles is suggested to be controlled by a common central nervous network (Zafar et al, 2000;Eriksson et al, 1998). Other studies have highlighted the anatomical, biomechanical and neurological link between the jaw and neck regions (Brodie, 1950;Chang et al, 1988).…”
Section: Effect Of Three Different Jaw Positions On Postural Stabilitmentioning
confidence: 98%